ANALISIS DAMPAK PEMEKARAN KABUPATEN LABUHANBATU UTARA 2008 -2014 TERHADAP PERKEMBANGAN PEMBANGUNAN KABUPATEN LABUHANBATU UTARA SESUAI DENGAN PP NO.129 TAHUN 2000 - Zafar Siddik Pohan (Politika: Jurnal Ilmu Politik, 2015)
North Labuhanbatu District Government is the result rather than the division that Labuhanbatu District in 2008. The division is an implementation of the Act 32 of 2004 set forth therein are the values of the people's welfare. Acceleration of development in Indonesia has been dimuai since the old order up until this reform era. Basically, the result of the division itself produce income for each area in the extract to be more independent and established and evolving as tembuh which are contained in the regional autonomy law No. 129/2000 Accelerating the Implementation of the Regional Economic Development, Management Acceleration Potential Areas, Improved Human Resources (HDI), Improvement of infrastructure facilities, etc. As the aim of achieving social welfare improvement. In accordance with the mandate of Regulation No. 6 of 2008 explained that the need for an evaluation of the impact of the expansion itself.The researchers themselves have a clear goal to learn in depth how the actual impact on the community division Labuthanbatu Regency Regency North Labuhanbatu carefully can see the development of existing development in the rapidly growing district of North Labuhanbatu.Researchers use impact evaluation analysis method descriptions or interviews in the form of questions to the informant related to the impact of the expansion in the district of North Labuhanbatu and then presents the results of research. Results of research conducted to increase the quality in the district of North Labuhanbatu to the development of good growing development in several sectors such as education sector, economic growth, human growth index sector in a sustainable manner. This can be seen from the results of research in which people who live in the District of North Labuhanbatu feel a good service and access to the construction of more touching than before the expansion.Keywords: Decentralization, Autonomy, Impact Evaluation